2011
DOI: 10.1586/erp.11.26
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic evidence of bosentan for pulmonary arterial hypertension

Abstract: In this article, we review randomized controlled trials, open-label trials and pharmacoeconomic models of bosentan for the management of patients with pulmonary arterial hypertension. Bosentan consistently improves WHO functional class and quality of life, slows clinical worsening and is associated with improved survival compared with historical treatment. Although head-to-head trials are scarce, data directly comparing bosentan with sildenafil indicate no clinically significant differences between treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…This reflects both increased awareness and increased detection of PAH, as well as the availability during this period of eight new drugs, including oral ERAs (e.g., bosentan‐Tracleer® and ambrisentan‐Volibris® or Letairis®); oral, subcutaneous, and intravenous prostanoids (e.g., treprostinil‐Remodulin®); and oral PDE‐5i (e.g., sildenafil‐Revatio® and tadalafil‐Adcirca®). The PH‐specific therapies are costly, with sildenafil being the most cost‐effective, according to a recent analysis . Modeling suggests that the cost‐effectiveness of the ERAs bosentan and ambrisentan are similar (US$43,725–57,778 per quality‐adjusted life year), but are less cost‐effective than sildenafil (at 20 mg t.i.d.).…”
Section: Who Ph Classification Systemmentioning
confidence: 99%
“…This reflects both increased awareness and increased detection of PAH, as well as the availability during this period of eight new drugs, including oral ERAs (e.g., bosentan‐Tracleer® and ambrisentan‐Volibris® or Letairis®); oral, subcutaneous, and intravenous prostanoids (e.g., treprostinil‐Remodulin®); and oral PDE‐5i (e.g., sildenafil‐Revatio® and tadalafil‐Adcirca®). The PH‐specific therapies are costly, with sildenafil being the most cost‐effective, according to a recent analysis . Modeling suggests that the cost‐effectiveness of the ERAs bosentan and ambrisentan are similar (US$43,725–57,778 per quality‐adjusted life year), but are less cost‐effective than sildenafil (at 20 mg t.i.d.).…”
Section: Who Ph Classification Systemmentioning
confidence: 99%
“…From an economic standpoint, the drug cost appears to be comparable to that of the other ERAs, although as noted previously, the cost should be considered in conjunction with overall health care costs. 48-52 At this time, clinicians may be advised to consider macitentan as a treatment option for patients with PAH who may be intolerant to other ERAs.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of a privately insured claims database over a mean period of 2 years revealed that prescription drugs accounted for 15% of the total direct health care costs per patient-month in patients with PAH. 51 Strange et al 52 reviewed clinical data on various medications for PAH and, using economic modeling, determined that the cost-effectiveness of bosentan and ambrisentan were similar; however, the cost-effectiveness of bosentan was found to be lower than that of sildenafil and higher than that of iloprost. These results, in conjunction with the absence of a clearly defined hierarchy in the available agents for PAH, demonstrate an additional consideration in PAH treatment decision making.…”
Section: Formulary Considerationsmentioning
confidence: 99%
“…Sildenafil represents a first-in-class drug that is orally administered, effective, and seemed to be safer than other PAH therapies at time of approval. Pharmacoeconomic evaluations of PAH therapies (excluding tadalafil) have concluded that sildenafil is the most cost-effective treatment for PAH on the basis of low price and net increase in quality of life (Garin et al, 2009;Strange et al, 2011). The annual AWP cost of Revatio in the United States is approximately $18,500 (Red Book, 2010).…”
Section: Label Expansion I Delay In Clinical Worseningmentioning
confidence: 99%